2015
DOI: 10.1186/s12885-015-1043-1
|View full text |Cite
|
Sign up to set email alerts
|

YY1 suppresses FEN1 over-expression and drug resistance in breast cancer

Abstract: BackgroundDrug resistance is a major challenge in cancer therapeutics. Abundant evidence indicates that DNA repair systems are enhanced after repetitive chemotherapeutic treatments, rendering cancers cells drug-resistant. Flap endonuclease 1 (FEN1) plays critical roles in DNA replication and repair and in counteracting replication stress, which is a key mechanism for many chemotherapeutic drugs to kill cancer cells. FEN1 was previously shown to be upregulated in response to DNA damaging agents. However, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 65 publications
6
47
0
Order By: Relevance
“…High expression of FEN1 appeared to associate in a statistically significant manner with highly malignant tumors ( p  < 0.05) and tumors of advanced TNM stage ( p  < 0.05). Moreover, consistent with this result and our previous report (Wang et al, 2015), Kaplan-Meier analyses revealed that breast cancer patients with high expression of FEN1 have poor prognoses (Fig. 1g).…”
Section: Resultssupporting
confidence: 92%
“…High expression of FEN1 appeared to associate in a statistically significant manner with highly malignant tumors ( p  < 0.05) and tumors of advanced TNM stage ( p  < 0.05). Moreover, consistent with this result and our previous report (Wang et al, 2015), Kaplan-Meier analyses revealed that breast cancer patients with high expression of FEN1 have poor prognoses (Fig. 1g).…”
Section: Resultssupporting
confidence: 92%
“…FEN1 is overexpressed in many forms of cancer and has been reported as a potential biomarker and target in different types of cancer. Knockdown of FEN1 could inhibit of proliferation of cancer cells . Our data revealed that the growth of HeLa cells was delayed when FEN1 activity was inhibited, which confirmed the previous observation.…”
Section: Discussionsupporting
confidence: 91%
“…Fen1 is a highly versatile protein and performs various cellular functions, depending on its interaction with different proteins [81]. In breast cancer cells, Fen1 is significantly up-regulated upon treatment of chemotherapeutic drugs such as mitomycin C (MMC) and Taxol, which is regulated by transcription factor/repressor YY1 [97]. YY1 down-regulates Fen1 and sensitizes the breast cancer cells to these drugs.…”
Section: Role Of Fen1 In Dna Replication Recombination and Repairmentioning
confidence: 99%
“…From a clinical point of view, the repression of Fen1 level by the YY1 transcription factor has been shown to increase the sensitivity of breast cancer cells to MMC and Taxol [97]. Similarly, as we have shown that APC blocks Fen1 activity [47] and targeting Fen1(D181) with a small molecule increases the sensitivity of colon cancer cells to temozolomide (TMZ) [150], it can be hypothesized that APC mediated blockade of Fen1 activity may also increase the sensitization of breast cancer cells to DNA damaging agents.…”
Section: Polymorphic Variations In Apc and Fen1 Genes That May Affmentioning
confidence: 99%